The Securitization The Securitization of Domestic Opposition by the Myanmar Junta Post-2021 Coup - Fajar Imam Zarkasyi; Kin Sara Nauti (Journal of Government Science Studies, 2026)
This study analyzes the securitization of domestic opposition by the Myanmar military junta following the February 1, 2021, coup. Using the Copenhagen School securitization theoretical framework, this study examines how the State Administration Council (SAC), led by Senior General Min Aung Hlaing, constructs political opposition as an existential threat to national stability, sovereignty, and national unity. The method used is descriptive qualitative with a single case study approach, through analysis of official junta documents, public speeches, regulations such as the Anti-Terrorism Law, and international organization reports. The results show that the junta transforms political issues into security issues through speech acts, particularly by designating the National Unity Government (NUG), the Committee Representing Pyidaungsu Hluttaw (CRPH), and the People's Defense Force (PDF) as terrorist organizations in Notification No. 2/2021. This action paved the way for the implementation of extraordinary measures such as mass arrests, media restrictions, internet blackouts, and military operations against civilians. Although the securitization narrative gained acceptance within institutions under military control, its legitimacy was not fully accepted by the wider public or the international community. This research confirms that the securitization of domestic opposition contributed to democratic backsliding, increased human rights violations, and the strengthening of authoritarianism in post-coup Myanmar.